Africanized honeybees: Biological characteristics, urban nesting behavior and accidents caused in Brazilian cities (Hymenoptera: Apidae) - Pereira, Andrigo Monroe [UNESP]; Chaud-Netto, José [UNESP] (My University, 2005)
In 1956 African honeybee queens (Apis mellifera scutellata) were imported from South Africa and Tanzania to Brazil, as part of a government project to increase Brazilian honey production. The European honeybees existing in that country had not adapted well to the tropical conditions and consequently, had a low productivity. The newly introduced bee was known to produce substantially more honey than the other subspecies, but was also famous for its great aggressiveness and quicker attack of intruders with less disturbance. Hoping to create a new hybrid bee that would be both docile and productive, the scientist Warwick Estevam Kerr tried to cross the African and the European subspecies under controlled conditions. However, an accident resulted in the escape of 26 swarms into the Brazilian countryside, where their queens mated with drones of the European resident honeybees. The poly-hybrid bees resulting from these crossings expressed scutellata-like reproductive, foraging, and defensive behaviors and, for this reason, were called Africanized honeybees. They spread rapidly from the introduction area of the African honeybees (near Rio Claro, São Paulo state) to as far south as mid-Argentina and to the north of Texas, also settling in Arizona, New Mexico, California and Nevada, due to their high adaptability to variable ecological conditions. In spite of a few undesirable behaviors, these bees have been invoking larger economic interest because they produce much more honey, have good resistance to diseases and are excellent pollinators. In Brazil, because people frequently disturb the environment, the occupation of urban refuges by Africanized honeybees has been increasing in the last years. The concern with accidents is generally associated with the high swarming frequency recorded during the year and the variety of shelters available in urban areas. This paper deals with the biological characteristics of the Africanized honeybees, their nesting behavior in urban environments, and accidents caused by these bees in Brazilian cities.
Keywords: Accidents; Africanized honeybees; Aggressiveness; Apis mellifera; Nesting behavior; Venom; Apidae; Apis mellifera scutellata; Apoidea; Hymenoptera